2019
DOI: 10.1159/000496292
|View full text |Cite
|
Sign up to set email alerts
|

Head or Neck First? Speed and Rates of Reperfusion in Thrombectomy for Tandem Large Vessel Occlusion Strokes

Abstract: Background: We aim to evaluate the speed and rates of reperfusion in tandem large vessel occlusion acute stroke patients undergoing upfront cervical lesion treatment (Neck-First: angioplasty and/or stent before thrombectomy) as compared to direct intracranial occlusion therapy (Head-First) in a large international multicenter cohort. Methods: The Thrombectomy In TANdem Lesions (TITAN) collaboration pooled individual data of prospectively collected thrombectomy international databases for all consecutive anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Our finding suggested that the retrograde approach might be superior to the antegrade approach with respect to more and earlier blood restoration and better functional outcome achievable. This was in line with several recent large sample size multicenter studies demonstrating faster distal occlusion reperfusion consistently in better clinical outcomes with the retrograde approach ( 25 , 28 ). Primarily, revascularization of the proximal extracranial lesion with Percutaneous Endovascular Angioplasty (PTA) and/or stenting before distal intracranial occlusion treatment seemed to be time-consuming thus postponed intracranial reperfusion.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding suggested that the retrograde approach might be superior to the antegrade approach with respect to more and earlier blood restoration and better functional outcome achievable. This was in line with several recent large sample size multicenter studies demonstrating faster distal occlusion reperfusion consistently in better clinical outcomes with the retrograde approach ( 25 , 28 ). Primarily, revascularization of the proximal extracranial lesion with Percutaneous Endovascular Angioplasty (PTA) and/or stenting before distal intracranial occlusion treatment seemed to be time-consuming thus postponed intracranial reperfusion.…”
Section: Discussionsupporting
confidence: 91%
“…Favorable outcome also reported by all the 11 studies and the pooled results indicated that the retrograde group achieved a significantly better 90-day functional independence than the antegrade group (47.3 vs. 40.2%; OR: 0.72, 95% CI: 0.58–0.89, p = 0.002) ( Figure 2B ). Sensitivity analysis indicated the heterogeneity ( p = 0.07, I 2 = 42%) also coming from the aforementioned two articles by Maus et al ( 15 ) and Haussen et al ( 25 ). No publication bias (Begg's test: p = 0.31; Egger's test: p = 0.17) was observed (see online Supplementary File 7 .…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Among the patients from the TITAN cohort, order of treatment of intracranial occlusion or cervical occlusion led to a similar rate of successful reperfusion (12). As expected, treating the intracranial occlusion first was associated with faster time from puncture to reperfusion; however, the order of treatment was not associated with clinical outcomes (12).…”
Section: Resultsmentioning
confidence: 99%
“…At present, data regarding antegrade versus retrograde approaches during EVT of TOs in the current literature are limited. 20 In a meta-analysis of CA-and CD-related TOs, no differences in reperfusion rates and clinical outcomes were observed between the antegrade and retrograde EVTs. 2 In line with these findings, no difference in terms of procedural times, number of MT passages, time to recanalization, and final mTICI score were observed between the two approaches in our study.…”
Section: Evt Strategy: Antegrade Versus Retrograde Approachmentioning
confidence: 95%